PEMBERDAYAAN KADER KESEHATAN UNTUK PENGELOLAAN DIABETES MELLITUS TIPE 2 MELALUI E-MODUL LATIHAN SYUKUR - Fazdria; Setio Budi Raharjo; Muhammad Husaini; Alchalidi; T. Iskandar Faisal (Poltekkes Kemenkes Mataram, 2025)
Type 2 Diabetes Mellitus (T2DM) is one of the chronic diseases whose prevalence is increasing in Gampong Miruek Lam Reudeup. Empowering health cadres through e-module gratitude training is an innovative approach that is expected to improve knowledge and skills in managing T2DM. This community service program aims to improve the understanding and skills of health cadres in managing T2DM through e-module-based gratitude training. The program method involves a series of training and mentoring for health cadres in implementing e-module-based gratitude training. Training materials include T2DM management, gratitude training, and simple blood sugar checks. The results achieved were an increase in percentage of 58.5% between pretest and posttest scores, indicating the success of the training in improving health cadres' knowledge, practical ability to successfully apply gratitude training techniques in daily practice and integrate them into patient care, increasing family support and understanding of T2DM management, T2DM patients experienced improved quality of life and satisfaction due to better management of blood sugar levels; and there was efficiency in handling T2DM cases with patients who were more active in caring for themselves. The program successfully achieved all of its stated targets, including increasing health cadres' knowledge, practical skills in gratitude practice, scientific publications and gratitude practice e-modules. The health cadre empowerment program through e-module-based gratitude training has had a positive impact on the management of DMT-2 in Gampong Miruek Lam Reudeup. This indicates that the participatory approach and the ability of gratitude training skills are very effective in improving the quality of life of DMT-2 families, especially DMT-2 patients.